Dual‐modality optical projection tomography reconstruction method from fewer views. Issue 4 (27th December 2018) - Dou, Shaobin; Liu, Jinhuai; Yang, Lianghuai
Abstract : In optical projection tomography (OPT), for longitudinal living model studies, multiple measurements of the same sample are required at different time points. It is important to decrease both the total acquisition time and the light dose to the sample. We improved the ordered subsets expectation maximization reconstruction algorithm for OPT, which reduces the acquisition time and number of projections greatly compared with filtered back projection (FBP), and obtained satisfactory reconstructed images. Using zebrafish, in transmission and fluorescence mode, we demonstrate the capability of the method to reconstruct image from downsampled projection subsets. The result shows that the reconstruction image quality of the proposed method using 30 projections is comparable to that of FBP using 720 projections. The total acquisition procedure can be finished in a few seconds. The method also provides OPT with the remarkable capability to resist noises and artifacts. Projection image and fused image of zebrafish. Abstract : The optical projection tomography (OPT) plays an important role in biological research. For longitudinal studies, it is important to decrease both the acquisition time and the light dose. The ordered subsets expectation maximization reconstruction algorithm is proposed, which reduces the acquisition time needed greatly. The precalibration method avoids the tedious correction process in later phase. Also, a set of dual‐modality equipment, which has transmission and emission image mode simultaneously, is designed for testing the algorithms. By using the dual‐modality system, in transmission and fluorescence mode, a zebrafish was scanned from sparse angle. The total acquisition procedure can be finished in a few seconds. Then, the scanned images were reconstructed by the algorithm proposed and fused. Finally, the fine transmission, fluorescence and fusion image were obtained. Also, it can be seen that the methods can provide OPT with the remarkable capability to resist noises and artifacts.